An appraisal analysis of attitude in Taman Sari tourists’ review in Tripadvisor - Siti Mahripah; Istingatun Mahfiroh (Jurnal Penelitian Humaniora, 2023)
This study aimed to identify the appraising items which employed in Taman Sari tourists’ review written in Trip Advisor. It identified how the visitors expressed their feeling, attitude, and judgment towards the Taman Sari tourist attractions by applying Martin White (2005) theory, especially the attitude devices. This study employed a descriptive qualitative method. The data used were reviews written by the tourists of Taman Sari in TripAdvisor. This study was done by separating the reviews into the one that contains appraising items of attitudes and then breaking them into clauses before they were analyzed. From the total of 56 data, it shows that there are 15 (26.79%) affect, 6 (10.71%) judgment, and 35 (62.50%) appreciation. Most of the reviews contains 50 (89.29%) positive attitudes, and only 6 (10.71%) with negative attitudes. This study asserted that the attitude device mostly used in the reviews is appreciation, especially reaction – quality since it deals with the evaluation of things which describes human feelings.